TINGKAT PARTISIPASI NELAYAN DALAM SOSIALISASI PELARANGAN PENGGUNAAN ALAT TANGKAP TRAWL DI KELURAHAN PEJALA KECAMATAN PENAJAM KABUPATEN PENAJAM PASER UTARA - Nur Hayati; Eko Sugiharto; Ristiyana Eryati (2339-1324, 2018)
The aim of this research were to known the indicator, rate factors and level of participation to determine the fisherman participation on restricted operation of trawl’s socialization, also to known effect of trawl’s operation at Ville of Pejala Subdistrict of Penajam, District of Penajam Paser Utara. The result showed that indicator rates of fisherman to operate trawl in activity are 15.94 consciously; 9.29 involved; and 8.94 helpful. Factors of participation were determined by internal factors e.i 9.6 of age; 10.6 of education; 6.9 of economic life; and 11 of length of stay, in the other hand, external factor e.i 8.3 of work duration; 12.4 of salary rate, were influenced the degree of fisherman participation on restricted operation of trawl. Based on calculation the degree is high with 65% of participation rate. The impact of trawl’s operation on long period constantly had been decrease the potential of aquatic resources.